Bay' al-tawarruq between BNM and AAOIFI : a comparative analysis - Muhammad Najib bin Abdurrahim (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research analyzes the similarities and differences between BNM and AAOIFI Tawarruq Standard. It also examines the application of BNM Tawarruq Standard within IFIs, in particular Islamic banks in Malaysia. A total of 7 from 16 Islamic banks under Islamic Financial and Services Act (IFSA) 2013 were selected as sampling to ensure the data collected may result a comprehensive finding for this research. In order to achieve the objectives of this research, two methodologies were adopted, which are qualitative method, comprising of library and field research and quantitative method to analyze the collected data. Through library research, the research has analysed the discussion on tawarruq based on the opinion of traditional and modern scholars. From the discussion, the researcher then has analysed the area of argument (mahallu al-niza') between the opinions and try to elaborate the selected opinion. The researcher has analysed the similarities and differences between the application of tawarruq as underlined in BNM and AAOIFI Tawarruq Standard. In this exercise, the researcher looked at the gaps between the application of tawarruq from both standard perspective and come out with selected opinion. In addition to the field research, the researcher has interviewed a selected respondent from the sample. This interview was participated by the senior industry player from sharī'ah background with more than 5 years of experience in the industry. As for the quantitative method, the researcher has adopted this method to quantify the collected data from interview assessment. The finding of this research has indicated two major findings. Firstly, the differences between BNM and AAOIFI Tawarruq Standard are derived from external factor, which then indicates that both standards can be harmonized each other. Secondly, the finding has proven that despite the same standard and requirement adopted by the industry, the application of tawarruq in Malaysia has been structured differently from one Islamic bank to another. This finding is derived from the different interpretation of the requirement by the respective Shariah Committee of Islamic banking institutions in Malaysia.